Policy Capacity in the Special Autonomy Framework in Increasing the Empowerment of Papuan People in Sorong City: A Conceptual Analysis - Kocu, Sem (KnE Social Sciences, 2025)
Studies on special autonomy (otsus) in Indonesia have developed in the last two decades. Several studies such as Fitra (2015) and Bivitri Susanti (2016) emphasize the construction of laws and regulations. Aspinall (2007) and Chauvel (2011) emphasized on the importance of cultural recognition and the history of marginalization as the basis for the legitimacy of special autonomy policies. In recent years, there has been a shift in focus towards governance and policy capacity as an alternative perspective to assess the effectiveness of special autonomy. The capacity model of Wu, Ramesh & Howlett (2015) is an important reference in assessing the analytical, operational, and political dimensions of local policy systems. Some of the analytical gaps are still largely untouched, such as the relative lack of studies that integrate the policy capacity approach in the analysis of specific autonomy and the lack of conceptual models that link institutional and socio-cultural structures within a single analytical framework. This study fills these gaps by developing a conceptual analysis framework related to the concept of policy capacity in the context of special autonomy. Discourse analysis approach based on a qualitative approach with an emphasis on analytical and operational capability analysis, as well as local socio-political dynamics that become the context of policy capacity. This study has made a theoretical contribution to the development of a more responsive and sustainable special autonomy policy governance, which is examined in the case of the capacity of special autonomy policies in Sorong City. Policy capacity is a fundamental prerequisite for the successful implementation of special autonomy. Capacity building should be a top priority in supporting the sustainability and effectiveness of special autonomy policies. This conceptual review shows that the success of special autonomy depends not only on the amount of authority or funding provided, but also on the extent to which local actors have the capacity to manage and utilize that authority effectively and inclusively. This is an inseparable part of efforts to increase the capacity of special autonomy policies in improving the quality and empowerment of the Papuan people in general.